STUDI KASUS TERAPI ARV PADA PASIEN LOST TO FOLLOW-UP DI JAKARTA PUSAT TAHUN 2021 - Awani Luksita; Yodi Mahendradhata; Yanri Wijayanti Subronto (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2022)
Background: There are 9,338 patients undergoing ARV therapy in Central Jakarta and based on data from April to June 2021, 3,651people are missing due to follow-up. Lost To Follow-Up (LTFU) is when the patient does not revisit after three months or more after thelast visit. Objective: Knowing the factors influencing ARV therapy in LTFU patients in Central Jakarta.Methods: This research is a case study research with a total of 12 informants consisting of LTFU patients, NGOs, doctors, and nursesfrom the priority health office in Central Jakarta. Data collection techniques using in-depth interviews and document review. Data analysis using framework analysis technique. Results: This study shows that the experience of LTFU patients wheninitially diagnosed with HIV experienced a pause in ARV therapy because they could not accept themselves as being HIV positive, andsome patients still did not understand ARV therapy treatment. ARV therapy decision-making is based on the motivation to be healthy andwant to see the child’s growth and development into adulthood. Patients feel that undergoing ARV therapy adds to activities that makethem unable to adjust their medication schedule, hampering work time because they must go to drug collection services. Some alsooften forget to bring medicine and feel the need to hide to take medicine when outside the house. The inhibiting factors for LTFU patientsare the effects of drugs; the COVID-19 pandemic condition; feeling healthy; tired of undergoing therapy; being far from health services,the number of costs incurred to go to services; not receiving complete information; and loss of support from the closest people.Conclusion: The government needs to improve strategies for LTFU patients to return to ARV therapy by optimizing the multi-month dispensing (MMD) program; inviting and providing education for family members or relatives of LTFU patients to take ARV therapy treatment by becoming a Drug Swallowing Supervisor (PMO); and it is important to support the design of HIV treatment telemedicine during the COVID-19 pandemic.